Fuel cell bipolar plate manufacturing method and fuel cell

By depositing transition layers on the surface of the metal bipolar plate and alternately depositing metal-doped amorphous carbon film, the problem of poor corrosion resistance of metal bipolar plates in acidic environments is solved, and a multi-layer nano with high conductivity and corrosion resistance is achieved Structure to meet the long-term operation needs of fuel cells.

CN119411070APending Publication Date: 2025-02-11BEIJING GOLDEN WHEEL SPECIAL MACHINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486636.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing metal bipolar plates have poor corrosion resistance and are prone to corrosion in acidic environments, and passivation layers are easily formed on the metal surface, which increases contact resistance and reduces the output power of the battery.

Method used

The transition layer is deposited on the surface of the metal bipolar plate, and multiple layers of metal-doped amorphous carbon film and pure amorphous carbon film are deposited alternately on the transition layer. The multi-layered layer is deposited alternately by magnetron sputtering and multi-arc coating devices to form Layer nanostructures to improve binding force and corrosion resistance.

Benefits of technology

It significantly improves the bonding force between the carbon film and the matrix, avoids the defect of poor corrosion caused by large particles, and makes the amorphous carbon film have good conductivity and corrosion resistance at the same time, satisfying the long-term use of the metal bipolar plate of the fuel cell. Operating requirements in acidic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411070A_ABST
    Figure CN119411070A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing method of a fuel cell bipolar plate and a fuel cell, relates to the technical field of fuel cells, and is designed for solving the problem of poor corrosion resistance of a metal bipolar plate. The manufacturing method of the fuel cell bipolar plate comprises the following steps: depositing a transition layer on the surface of a metal bipolar plate; depositing a plurality of layers of metal doped amorphous carbon films on the surface of the transition layer; and depositing a pure amorphous carbon film on the surface of the metal-doped amorphous carbon film. The corrosion resistance of the metal bipolar plate can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for manufacturing a bipolar plate of a fuel cell and a fuel cell. Background Art

[0002] Proton Exchange Membrane Fuel Cell (PEMFC) is an electrochemical device that generates electricity through a combustion-free electrochemical reaction. As a new type of pollution-free clean energy, PEMFC has the advantages of low temperature, low pressure, short start-stop time, low noise and high efficiency. It can not only meet the high power requirements of new energy electric vehicles, but also is suitable for low-power portable electronic devices. Therefore, PEMFC has broad development prospects in the field of energy conservation.

[0003] The bipolar plate is one of the most critical components of the PEMFC fuel cell stack. Its volume, quality and cost play a decisive role in the total cost of the stack. The bipolar plate supports the battery, separates the gas in the battery, conducts electricity and heat, and supports the battery pack structure. In addition, due to the acidic environment of PEMFC, the bipolar plate is prone to corrosion. Therefore, in order to maintain the efficient operation of PEMFC, materials with good conductivity, corrosion resistance, hydrophobicity and certain mechanical strength are usually selected as the raw materials of the bipolar plate.

[0004] Bipolar plates can be roughly divided into three categories according to the type of materials: graphite bipolar plates, metal bipolar plates and composite bipolar plates. Metal bipolar plates have the greatest potential for industrial production due to their easy processing and high mechanical strength. Au, Pt, Ti and stainless steel are directly used as materials for metal bipolar plates. Among them, Au and Pt are used as bipolar plates to assemble batteries with excellent performance, but the cost is too high to achieve large-scale application. Although other metal materials have excellent mechanical properties, their chemical properties are more active and their corrosion resistance is generally poor, which cannot meet the long-term operation of batteries under acidic conditions.

[0005] At present, some metal bipolar plates are mainly faced with the following two problems during use: first, in acidic solutions, some metal materials have poor corrosion resistance and are prone to corrosion; second, a passivation layer is easily formed on the metal surface. The poor conductivity of the passivation layer also increases the contact resistance between it and the diffusion layer, thereby reducing the output power of the battery. Moreover, the metal ions generated by metal corrosion diffuse into the membrane electrode, which will reduce the conductivity of the proton exchange membrane and poison the catalyst, which will have a very adverse effect on battery performance. Summary of the invention

[0006] The first object of the present invention is to provide a method for manufacturing a fuel cell bipolar plate to solve the technical problem that the existing metal bipolar plates have poor corrosion resistance.

[0007] The present invention provides a method for manufacturing a fuel cell bipolar plate, comprising:

[0008] Depositing a transition layer on the surface of the metal bipolar plate;

[0009] Depositing multiple layers of metal-doped amorphous carbon films on the surface of the transition layer;

[0010] A pure amorphous carbon film is deposited on the surface of the metal-doped amorphous carbon film.

[0011] Furthermore, before the transition layer is deposited, the metal bipolar plate is also plasma etched and cleaned.

[0012] Furthermore, before the plasma etching cleaning, the metal bipolar plate is ultrasonically cleaned and dried, and then the metal bipolar plate is placed in an ion plating machine, and the metal bipolar plate, the vacuum chamber of the ion plating machine and the rotating rack are baked and degassed.

[0013] Furthermore, the number of deposited layers of the metal-doped amorphous carbon film is four.

[0014] Furthermore, when depositing the multi-layer metal-doped amorphous carbon film, a magnetron sputtering device is used to deposit the metal film, and the metal target in the magnetron sputtering device is a magnetron sputtering metal target. When depositing each layer, the current of the metal target is gradually reduced.

[0015] Furthermore, when depositing a multi-layer metal-doped amorphous carbon film, a multi-arc coating device is used to deposit the amorphous carbon film. During the deposition of each layer of the metal-doped amorphous carbon film, the pressure of the vacuum chamber is 0.5Pa-1.5Pa, the argon gas flow rate is 450sccm-800sccm, the bias voltage is 80V-130V, the current of the multi-arc coating device is 50A-75A, the multi-arc target is a graphite target, and the metal target is made of Ti or Cr; and / or,

[0016] The number of deposition layers of the metal-doped amorphous carbon film is four. The metal target current when depositing the first layer of the metal-doped amorphous carbon film is 11A~15A, the metal target current when depositing the second layer of the metal-doped amorphous carbon film is 7A~9A, the metal target current when depositing the third layer of the metal-doped amorphous carbon film is 3A~5A, and the metal target current when depositing the fourth layer of the metal-doped amorphous carbon film is 1A~2A.

[0017] Furthermore, a multi-arc coating device is used when depositing the pure amorphous carbon film, the pressure of the vacuum chamber is 0.4Pa~0.8Pa, the argon gas flow rate is 200sccm~500sccm, the bias voltage is 50V~300V, and the multi-arc target is a graphite target, and the current of the graphite target is 50A~75A.

[0018] Furthermore, when depositing the transition layer, a multi-arc coating device is used, the pressure of the vacuum chamber is 0.5Pa~1.5Pa, the argon gas flow rate is 450sccm~800sccm, the bias voltage is 120V~180V, the arc source current is 70A~90A, and the material of the transition layer is Nb.

[0019] Further, the metal bipolar plate is placed in an ion plating machine, and the metal bipolar plate, the vacuum chamber of the ion plating machine and the rotating rack are baked and degassed. After the metal bipolar plate is placed in the ion plating machine, a mechanical pump and a molecular pump group are turned on to evacuate the vacuum, and heating is turned on. The heating temperature is 150° C. to 200° C., and the baking time is 1 h to 2 h; and / or,

[0020] When the metal bipolar plate is subjected to plasma etching and cleaning, the power of the ion source is 2 kW to 3 kW, the flow rate of argon gas is 300 sccm to 500 sccm, the bias voltage is 500 V to 600 V, and the time is 0.5 h to 1 h.

[0021] The beneficial effects brought by the manufacturing method of the fuel cell bipolar plate of the present invention are:

[0022] By alternately doping metal elements with the deposition of amorphous carbon films, the thermophysical mismatch between the amorphous carbon film and the substrate can be alleviated, thereby significantly improving the bonding strength between the carbon film and the substrate. In addition, the defect of poor corrosion resistance caused by large particles caused by multi-arc ion plating of amorphous carbon films can be avoided, so that the amorphous carbon film has good electrical conductivity and corrosion resistance at the same time, meeting the requirements of high conductivity and corrosion resistance of metal bipolar plates, thereby satisfying the requirements of long-term operation of metal bipolar plates of fuel cells in acidic environments.

[0023] The second object of the present invention is to provide a fuel cell to solve the technical problem of poor corrosion resistance of existing metal bipolar plates.

[0024] The fuel cell provided by the present invention includes a bipolar plate manufactured by the above-mentioned method for manufacturing a fuel cell bipolar plate.

[0025] The beneficial effects brought by the fuel cell of the present invention are:

[0026] By setting the bipolar plate manufactured by the manufacturing method of the fuel cell bipolar plate in the fuel cell, the fuel cell accordingly has all the advantages of the bipolar plate manufactured by the manufacturing method of the fuel cell bipolar plate, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0028] Figure 1 A schematic flow chart of a method for manufacturing a bipolar plate for a fuel cell provided in an embodiment of the present invention;

[0029] Figure 2 A schematic structural diagram of a fuel cell metal bipolar plate prepared by the method for manufacturing a fuel cell bipolar plate provided in an embodiment of the present invention.

[0030] Description of reference numerals:

[0031] 100-substrate; 200-plasma activation zone; 300-transition layer; 400-metal-doped amorphous carbon film layer; 500-pure amorphous carbon film layer. DETAILED DESCRIPTION

[0032] In the related technology, a layer of amorphous carbon film is usually deposited on the surface of the metal bipolar plate using Ti as the base. The preparation process is simple, and it has certain conductivity and corrosion resistance after being deposited on the test sample flat plate. However, since the metal bipolar plate adopts a flow channel plate structure during actual operation, the actual conductivity test performance of the amorphous carbon film with Ti as the base on the flow channel plate is quite different from the test results on the flat sample. Therefore, it is currently necessary to change the type of transition layer. Since Nb has better conductivity and corrosion resistance than Ti, the transition layer metal Nb is used to adapt to the complex flow channel plate structure to further improve the conductivity of the flow channel plate.

[0033] Secondly, when using transition layer metal Nb to deposit amorphous carbon film on metal bipolar plates, due to the special structural properties, thermophysical properties and large growth stress of the carbon film itself, the highly cross-linked structure formed by the distortion of hybrid bonds and the thermophysical coarse matching with the substrate during the deposition process will generate very large internal stress, which seriously affects the bonding performance between the film and the substrate; and since amorphous carbon film can be divided into GLC (Graphite-Like Carbon, graphite-like carbon) film and DLC (Diamond-Like Carbon, diamond-like carbon) film according to the ratio of sp3 hybridization and sp2 hybridization, GLC film has the advantages of low resistivity, moderate hardness, good corrosion resistance, etc. According to the sub-surface injection model, the formation process of GLC film is to inject low-energy carbon ions into the surface of the substrate for growth. Therefore, how to control the energy of carbon ions and regulate the balance of the ratio of sp2 hybridization and sp3 hybridization so that amorphous carbon film is more conducive to the formation of GLC film, while having good conductivity and corrosion resistance, is also the main problem currently faced.

[0034] The manufacturing method of the fuel cell bipolar plate provided in an embodiment of the present invention includes: depositing a transition layer on the surface of the metal bipolar plate; depositing multiple layers of metal-doped amorphous carbon film on the surface of the transition layer; and depositing a pure amorphous carbon film on the surface of the metal-doped amorphous carbon film.

[0035] By alternately doping metal elements with the deposition of amorphous carbon films, the thermophysical mismatch between the amorphous carbon film and the substrate can be alleviated, thereby significantly improving the bonding strength between the carbon film and the substrate. In addition, the defect of poor corrosion resistance caused by large particles caused by multi-arc ion plating of amorphous carbon films can be avoided, so that the amorphous carbon film has good electrical conductivity and corrosion resistance at the same time, meeting the requirements of high conductivity and corrosion resistance of metal bipolar plates, thereby satisfying the requirements of long-term operation of metal bipolar plates of fuel cells in acidic environments.

[0036] Because the ion bombardment during the deposition of the amorphous carbon film and the difference in physical properties and thermal expansion coefficients between the amorphous carbon film and the substrate will cause relatively large internal stress, and metals are materials with low elastic modulus, while amorphous carbon films are materials with high elastic modulus. According to the modulus difference strengthening mechanism, the greater the difference in elastic modulus between the two materials, the greater the repulsive force at the interface, and the better the strengthening effect of the film. By alternately depositing the two materials, a multilayer nanostructure is achieved, thereby further adjusting the defects and dislocations in the film, and the complex interface effects between the layers, so this multilayer structure can directly alleviate the thermal physical mismatch between the amorphous carbon film and the substrate.

[0037] Optionally, before the transition layer is deposited, the metal bipolar plate is also plasma etched and cleaned.

[0038] Plasma etching cleaning can not only clean the surface impurities such as oxides of the metal bipolar plate, but also activate the substrate surface, improve the bonding strength of the membrane substrate, and facilitate the bonding of the transition layer metal and the substrate.

[0039] Specifically, when the metal bipolar plate is plasma-etched and cleaned, the power of the ion source is 2 kW to 3 kW, the argon gas flow rate is 300 sccm to 500 sccm, the bias voltage is 500 V to 600 V, and the time is 0.5 h to 1 h.

[0040] Among them, plasma etching cleaning can choose plasma source glow cleaning.

[0041] Optionally, before plasma etching cleaning, the metal bipolar plate is ultrasonically cleaned and dried, and then the metal bipolar plate is placed in an ion plating machine, and the metal bipolar plate, the vacuum chamber of the ion plating machine and the rotating rack are baked and degassed.

[0042] When ultrasonic cleaning is performed on the metal bipolar plate, an alkaline water-based cleaning agent can be used as the cleaning agent, mainly to remove stains and oil stains on the surface of the metal bipolar plate. After cleaning, the metal bipolar plate can be placed in a heating drying oven for drying, and the drying time can be selected to be 15 minutes to 20 minutes.

[0043] Specifically, the metal bipolar plate is placed in the ion plating machine, and the metal bipolar plate, the vacuum chamber of the ion plating machine and the rotating rack are baked and degassed. After the metal bipolar plate is placed in the ion plating machine, the mechanical pump and the molecular pump group are turned on to evacuate the vacuum, and the heating is turned on. The heating temperature is 150° C. to 200° C., and the baking time is 1 h to 2 h.

[0044] Optionally, the number of deposited layers of the metal-doped amorphous carbon film is four.

[0045] The reason why the number of deposited layers of metal-doped amorphous carbon film is chosen to be four is that if three layers are deposited, the time for each step must be increased to achieve the same thickness as four layers. If the first deposition time is longer, the amount of metal doping is higher, which will destroy the structure of the amorphous carbon film and affect the corrosion resistance of the amorphous carbon film; if more than four layers are designed, the deposition time of each step will be shortened, which will affect the doping amount of the metal element. If the first deposition time is shorter, the amount of metal doping is less, which has less effect on the internal stress of the amorphous carbon film and the bonding strength will be relatively poor. Therefore, four layers are the best choice to ensure the corrosion resistance of the amorphous carbon film and the bonding strength of the coating.

[0046] Optionally, when depositing multiple layers of metal-doped amorphous carbon film, a magnetron sputtering device is used to deposit the metal film, and the metal target in the magnetron sputtering device is a magnetron sputtering metal target. When depositing each layer, the current of the metal target is gradually reduced.

[0047] The use of magnetron sputtering metal film can avoid the defects caused by large particles in the amorphous carbon film and improve the corrosion resistance. When depositing each layer, the current of the metal target is gradually reduced, so that different contents of metal elements can be doped in the amorphous carbon film, thereby forming a gradient transition mode of amorphous carbon film doped with high concentration to low concentration of elements, alleviating the defect of poor film-base bonding caused by directly using amorphous carbon film doped with low concentration of elements.

[0048] The total thickness of each layer of the metal-doped amorphous carbon film in this embodiment may be 50 nm to 200 nm.

[0049] Optionally, when depositing a multi-layer metal-doped amorphous carbon film, a multi-arc coating device is used to deposit the amorphous carbon film. During the deposition of each layer of the metal-doped amorphous carbon film, the pressure of the vacuum chamber is 0.5Pa-1.5Pa, the argon gas flow rate is 450sccm-800sccm, the bias voltage is 80V-130V, the current of the multi-arc coating device is 50A-75A, and the multi-arc target is a graphite target, and the metal target is Ti or Cr.

[0050] The number of deposition layers of the metal-doped amorphous carbon film is four. The metal target current when depositing the first layer of the metal-doped amorphous carbon film is 11A~15A, the metal target current when depositing the second layer of the metal-doped amorphous carbon film is 7A~9A, the metal target current when depositing the third layer of the metal-doped amorphous carbon film is 3A~5A, and the metal target current when depositing the fourth layer of the metal-doped amorphous carbon film is 1A~2A.

[0051] By using magnetron sputtering and multi-arc alternating deposition, the stress of carbon-based films during the deposition process can be eliminated, and the bonding force between the amorphous carbon film and the substrate can be enhanced. In addition, by using magnetron sputtering to deposit metal-doped amorphous carbon films, film defects caused by large particles produced by multi-arc ion plating can be avoided, further improving the corrosion resistance of carbon-based films. Moreover, a small amount of metal doping can be dissolved in the amorphous carbon network structure, reducing the internal stress caused by bond angle distortion in the amorphous carbon film network and improving the film-base bonding force; secondly, it can promote the hybridization of sp2 bonds in the amorphous carbon film, increase the carrier concentration of the amorphous carbon film, and further improve the conductivity.

[0052] By adjusting the preparation process of the amorphous carbon film, reducing the bias voltage and increasing the deposition temperature, the formation of sp2 bonds is facilitated, thereby reducing the contact resistance, so that the amorphous carbon film has good conductivity and corrosion resistance at the same time, meeting the requirements of high conductivity and corrosion resistance of metal bipolar plates, thereby meeting the long-term operation conditions of fuel cell metal bipolar plates in acidic environments.

[0053] Optionally, a multi-arc coating device is used when depositing pure amorphous carbon film, the pressure of the vacuum chamber is 0.4Pa~0.8Pa, the argon gas flow rate is 200sccm~500sccm, the bias voltage is 50V~300V, the multi-arc target is a graphite target, and the current of the graphite target is 50A~75A.

[0054] The thickness of the pure amorphous carbon film in this embodiment can be selected to be 50nm to 200nm. The chemical stability of the carbon film can be ensured by depositing the amorphous carbon film by multi-arc ion plating, and the large particles in the amorphous carbon film are conductive, which is conducive to improving the conductivity of the amorphous carbon film.

[0055] Optionally, when depositing the transition layer, a multi-arc coating device is used, the pressure of the vacuum chamber is 0.5Pa~1.5Pa, the argon gas flow rate is 450sccm~800sccm, the bias voltage is 120V~180V, the arc source current is 70A~90A, and the material of the transition layer is Nb.

[0056] Specifically, in this embodiment, the thickness of the transition layer can be selected to be 50nm to 200nm. Good bonding force is an important prerequisite for ensuring that the film works. Due to the modulus mismatch between carbon-based films and many bipolar plate materials such as iron alloys, titanium alloys, and aluminum alloys, the transition layer is deposited by multi-arc ion plating. Multi-arc can increase ion energy, increase the bonding force between the transition layer and the substrate, and further adjust the mismatch between the carbon-based film and the bipolar plate. In particular, the transition layer uses Nb, which is more suitable for complex flow channel plate structures than the commonly used transition layer Ti, and solves the problem of relatively poor conductivity of amorphous films in complex flow channel plates in the prior art.

[0057] Figure 1 A schematic diagram of a method for manufacturing a fuel cell bipolar plate according to an embodiment of the present invention; Figure 1 As shown, the method for manufacturing a fuel cell metal bipolar plate provided by an embodiment of the present invention comprises the following steps:

[0058] S1. The metal bipolar plate to be treated is placed in an ultrasonic cleaning line for ultrasonic cleaning, and then placed in an oven for drying;

[0059] S2. Put the metal bipolar plate into the ion plating machine, turn on the vacuum ion plating machine for heating, bake and degas the bipolar plate to be treated, the vacuum chamber, and the rotating rack to improve the cleanliness of the chamber;

[0060] S3, performing plasma etching and cleaning on the surface of the metal bipolar plate to activate the substrate surface and clean impurities on the surface of the metal bipolar plate;

[0061] S4, depositing a transition layer on the surface of the metal bipolar plate to obtain a metal bipolar plate with a transition layer, wherein the deposition of the transition layer on the surface of the metal bipolar plate is performed using a multi-arc coating device;

[0062] S5, depositing a total of four layers of metal-doped amorphous carbon films on the surface of the metal bipolar plate containing the transition layer to obtain a metal bipolar plate with a metal-doped amorphous carbon film;

[0063] S6. A pure amorphous carbon film is deposited on a metal bipolar plate of a metal-doped amorphous carbon film, and finally a high-performance amorphous carbon film having both electrical conductivity and corrosion resistance is obtained.

[0064] Figure 2 A schematic diagram of the structure of a fuel cell metal bipolar plate prepared by the method for manufacturing a fuel cell bipolar plate provided in an embodiment of the present invention; Figure 2 As shown, the fuel cell metal bipolar plate prepared by the method includes, starting from the substrate 100, the substrate 100, the plasma activation region 200, the transition layer 300, the metal-doped amorphous carbon film layer 400 and the pure amorphous carbon film layer 500. The relative thickness of each layer or region in the figure is only for the convenience of clearly showing the structure, and does not represent a limitation on the thickness of each layer or region in the figure.

[0065] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following two embodiments are given for detailed description. It should be understood that the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0066] Embodiment 1:

[0067] This embodiment introduces a method for manufacturing a bipolar plate for a fuel cell. Specifically, the manufacturing method includes the following steps:

[0068] 1. Use industrial seven-tank ultrasonic cleaning of the metal bipolar plate for 15 minutes. After cleaning, blow dry and dry in a vacuum drying oven for 20 minutes.

[0069] 2. Install the cleaned metal bipolar plate on the tooling, install the tooling on the vacuum ion plating machine turntable, close the door and evacuate. Turn on the mechanical pump to evacuate the vacuum chamber, and pump the vacuum chamber pressure to below 5Pa. Turn on the molecular pump group to evacuate, turn on the turntable, and turn on the heater for heating. Set the heating temperature to 150℃, bake and degas the bipolar plate, vacuum chamber, and turntable to improve the cleanliness of the chamber. The baking time is 1h.

[0070] 3. Maintain the vacuum chamber temperature at 180°C and evacuate the vacuum chamber to 5×10 -3Pa, argon flow rate 500sccm, vacuum chamber pressure 1Pa, ion source 2kw, bias 500V, cleaning time 30min, turn on the ion source, activate and clean the metal bipolar plate to remove pollutants and oxides on the substrate surface, and further improve the membrane-substrate bonding strength.

[0071] 4. After plasma cleaning, a multi-arc coating device is used to deposit a transition layer on the surface of the metal bipolar plate. The transition layer material is selected as metal Nb. The vacuum chamber temperature is maintained at 180°C, the argon gas flow rate is set to 200sccm, the vacuum chamber pressure is 0.5Pa, the bias voltage is 120V, the multi-arc Nb target arc source current is 70A, and the deposition time is 5min.

[0072] 5. After the transition layer is deposited, the first layer of metal-doped amorphous carbon film is deposited on the surface of the metal bipolar plate. The argon flow rate is set to 450 sccm, the vacuum chamber pressure is 0.5 Pa, the bias voltage is 80 V, the multi-arc graphite target current is set to 50 A, the target current of the magnetron metal Cr target is 11 A, and the deposition time is 3 min. Next, the second layer of metal-doped amorphous carbon film is deposited on the surface of the metal bipolar plate, with the argon flow rate set to 450sccm, the vacuum chamber pressure of 1Pa, the bias voltage of 80V, the multi-arc graphite target current set to 50A, the target current of the magnetron metal Cr target of 7A, and the deposition time of 2min; then the third layer of metal-doped amorphous carbon film is deposited on the surface of the metal bipolar plate, with the argon flow rate set to 450sccm, the vacuum chamber pressure of 1Pa, the bias voltage of 80V, the multi-arc graphite target current set to 50A, the target current of the magnetron metal Cr target of 3A, and the deposition time of 2min; finally, the fourth layer of metal-doped amorphous carbon film is deposited on the surface of the metal bipolar plate, with the argon flow rate set to 450sccm, the vacuum chamber pressure of 0.5Pa, the bias voltage of 80V, the multi-arc graphite target current set to 75A, the target current of the magnetron metal Cr target of 2A, and the deposition time of 2min.

[0073] 6. Finally, an amorphous carbon film was deposited on the surface of the metal-doped amorphous carbon film, wherein the argon flow rate was adjusted to 200 sccm, the gas pressure in the vacuum chamber was adjusted to 0.5 Pa, the bias voltage was set to 50 V, the multi-arc graphite target current was set to 50 A, and the deposition time was 20 min to obtain an amorphous carbon film with a thickness of 150 nm.

[0074] Finally, a high-conductivity, corrosion-resistant film with a thickness of about 500 nm, consisting of a transition layer, a metal-doped amorphous carbon film layer, and an amorphous carbon film layer, is prepared on the surface of the bipolar plate.

[0075] The surface contact resistance of the metal bipolar plate with high conductivity and corrosion resistant film prepared in this embodiment was tested. Under a pressure of 1.5 MPa, the measured contact resistance was 2.23 mΩ / cm 2 ,

[0076] The corrosion resistance of the metal bipolar plate with high conductivity and corrosion resistant film prepared in this embodiment was tested by electrochemical station. Under the test conditions of dynamic potential -0.5V~1.2V, PH=3, H2SO4+0.1ppmHF, the test corrosion current density was 0.117μA / cm 2 .

[0077] The metal bipolar plate with the high-conductivity and corrosion-resistant film prepared in this embodiment was subjected to a bending test. The metal bipolar plate was bent 180°, and the high-conductivity and corrosion-resistant film showed no film peeling and no leakage of the bottom layer.

[0078] The high-conductivity and corrosion-resistant coating provided by the present invention meets the US DOE (Design Of Experiment) index (contact resistance <10mΩ / cm 2 , corrosion current density <1μA / cm 2 ), has excellent high conductivity and corrosion resistance, and is suitable for application in the field of fuel cell metal bipolar plates.

[0079] Embodiment 2:

[0080] This embodiment introduces another method for manufacturing a bipolar plate for a fuel cell. Specifically, the manufacturing method includes the following steps:

[0081] 1. Use industrial seven-tank ultrasonic cleaning of the metal bipolar plate for 15 minutes. After cleaning, blow dry and dry in a vacuum drying oven for 20 minutes.

[0082] 2. Install the cleaned metal bipolar plate on the tooling, install the tooling on the vacuum ion plating machine turntable, close the door and evacuate. Turn on the mechanical pump to evacuate the vacuum chamber, and pump the vacuum chamber pressure to below 5Pa. Turn on the molecular pump group to evacuate, turn on the turntable, and turn on the heater for heating. Set the heating temperature to 200℃, bake and degas the bipolar plate, vacuum chamber, and turntable to improve the cleanliness of the chamber. The baking time is 2h.

[0083] 3. Maintain the vacuum chamber temperature at 180°C and evacuate the vacuum chamber to 5×10 -3 Pa, argon flow rate 500sccm, vacuum chamber pressure 1Pa, ion source 3kw, bias 600V, cleaning time 60min, turn on the ion source, activate and clean the metal bipolar plate to remove pollutants and oxides on the substrate surface, and further improve the membrane-substrate bonding strength.

[0084] 4. After plasma cleaning, a multi-arc coating device is used to deposit a transition layer on the surface of the metal bipolar plate. The transition layer material is selected as metal Nb. The vacuum chamber temperature is maintained at 180°C, the argon flow rate is set to 500sccm, the vacuum chamber pressure is 1.5Pa, the bias voltage is 180V, the multi-arc Nb target arc source current is 90A, and the deposition time is 5min.

[0085] 5. After the transition layer is deposited, the first layer of metal-doped amorphous carbon film is deposited on the surface of the transition layer of the metal bipolar plate. The argon flow rate is set to 800 sccm, the vacuum chamber pressure is 1.5 Pa, the bias voltage is 130 V, the multi-arc graphite target current is set to 60 A, the target current of the magnetron metal Cr target is 15 A, and the deposition time is 3 min. Next, the second layer of metal-doped amorphous carbon film is deposited on the surface of the metal bipolar plate, with the argon flow rate set to 800sccm, the vacuum chamber pressure of 1Pa, the bias voltage of 100V, the multi-arc graphite target current set to 75A, the target current of the magnetron metal Cr target of 9A, and the deposition time of 2min; then the third layer of metal-doped amorphous carbon film is deposited on the surface of the metal bipolar plate, with the argon flow rate set to 800sccm, the vacuum chamber pressure of 1Pa, the bias voltage of 100V, the multi-arc graphite target current set to 75A, the target current of the magnetron metal Cr target of 5A, and the deposition time of 2min; finally, the fourth layer of metal-doped amorphous carbon film is deposited on the surface of the metal bipolar plate, with the argon flow rate set to 800sccm, the vacuum chamber pressure of 1Pa, the bias voltage of 100V, the multi-arc graphite target current set to 75A, the target current of the magnetron metal Cr target of 1A, and the deposition time of 2min.

[0086] 6. A pure amorphous carbon film was deposited on the surface of the metal-doped amorphous carbon film, wherein the argon flow rate was adjusted to 500 sccm, the gas pressure in the vacuum chamber was adjusted to 0.5 Pa, the bias voltage was set to 300 V, the multi-arc graphite target current was set to 75 A, and the deposition time was 20 min to obtain an amorphous carbon film with a thickness of 180 nm.

[0087] 7. Finally, a high-conductivity, corrosion-resistant film with a thickness of about 550 nm is prepared on the surface of the bipolar plate, which is composed of a transition layer, a metal-doped amorphous carbon film layer, and an amorphous carbon film layer.

[0088] The surface contact resistance of the metal bipolar plate with high conductivity and corrosion resistant film prepared in this embodiment was tested. Under a pressure of 1.5 MPa, the contact resistance of the sample was 2.833 mΩ / cm 2 .

[0089] The corrosion resistance of the metal bipolar plate with high conductivity and corrosion resistant film prepared in this embodiment was tested by using an electrochemical station. Under the test conditions of dynamic potential -0.5V~1.2V, PH=3, H2SO4+0.1ppmHF, the test corrosion current density was 0.352μA / cm 2 .

[0090] The metal bipolar plate with the high-conductivity and corrosion-resistant film prepared in this embodiment was subjected to a bending test. The metal bipolar plate was bent 180°, and the high-conductivity and corrosion-resistant film showed no film peeling and no leakage of the bottom layer.

[0091] The high conductivity and corrosion resistant coating provided by the present invention meets the US DOE index (contact resistance <10mΩ / cm 2 , corrosion current density <1μA / cm 2 ), has excellent high conductivity and corrosion resistance, and is suitable for application in the field of fuel cell metal bipolar plates.

[0092] An embodiment of the present invention further provides a fuel cell, including a method for manufacturing the above-mentioned fuel cell bipolar plate.

[0093] By setting the metal bipolar plate prepared by the above-mentioned fuel cell bipolar plate manufacturing method in a fuel cell, the fuel cell accordingly has all the advantages of the metal bipolar plate prepared by the above-mentioned fuel cell bipolar plate manufacturing method, which will not be described one by one here.

[0094] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

[0095] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0096] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for manufacturing a bipolar plate for a fuel cell, characterized in that: include: Depositing a transition layer on the surface of the metal bipolar plate; Depositing a multi-layer surface metal-doped amorphous carbon film on the surface of the transition layer; A pure amorphous carbon film is deposited on the surface of the metal-doped amorphous carbon film.

2. The method for manufacturing a fuel cell bipolar plate according to claim 1, characterized in that: Before the transition layer is deposited, the metal bipolar plate is also cleaned by plasma etching.

3. The method for manufacturing a fuel cell bipolar plate according to claim 2, characterized in that: Before the plasma etching cleaning, the metal bipolar plate is ultrasonically cleaned and dried, and then the metal bipolar plate is placed in an ion plating machine, and the metal bipolar plate, the vacuum chamber of the ion plating machine and the rotating rack are baked and degassed.

4. The method for manufacturing a fuel cell bipolar plate according to any one of claims 1 to 3, characterized in that: The number of deposited layers of the metal-doped amorphous carbon film is four.

5. The method for manufacturing a fuel cell bipolar plate according to any one of claims 1 to 3, characterized in that: When depositing the multi-layer metal-doped amorphous carbon film, a magnetron sputtering device is used to deposit the metal film. The metal target in the magnetron sputtering device is a magnetron sputtering metal target. When depositing each layer, the current of the metal target is gradually reduced.

6. The method for manufacturing a fuel cell bipolar plate according to claim 5, characterized in that: When depositing a multi-layer metal-doped amorphous carbon film, a multi-arc coating device is used to deposit the amorphous carbon film. During the deposition of each layer of the metal-doped amorphous carbon film, the pressure of the vacuum chamber is 0.5Pa-1.5Pa, the argon gas flow rate is 450sccm-800sccm, the bias voltage is 80V-130V, the current of the multi-arc coating device is 50A-75A, the multi-arc target is a graphite target, and the metal target is made of Ti or Cr; and / or, The number of deposition layers of the metal-doped amorphous carbon film is four. The metal target current when depositing the first layer of the metal-doped amorphous carbon film is 11A~15A, the metal target current when depositing the second layer of the metal-doped amorphous carbon film is 7A~9A, the metal target current when depositing the third layer of the metal-doped amorphous carbon film is 3A~5A, and the metal target current when depositing the fourth layer of the metal-doped amorphous carbon film is 1A~2A.

7. The method for manufacturing a fuel cell bipolar plate according to claim 1, characterized in that: A multi-arc coating device is used when depositing the pure amorphous carbon film, the pressure of the vacuum chamber is 0.4Pa-0.8Pa, the argon gas flow rate is 200sccm-500sccm, the bias voltage is 50V-300V, and the multi-arc target is a graphite target, and the current of the graphite target is 50A-75A.

8. The method for manufacturing a fuel cell bipolar plate according to claim 1, characterized in that: When depositing the transition layer, a multi-arc coating device is used, the pressure of the vacuum chamber is 0.5Pa~1.5Pa, the argon gas flow rate is 450sccm~800sccm, the bias voltage is 120V~180V, the arc source current is 70A~90A, and the material of the transition layer is Nb.

9. The method for manufacturing a fuel cell bipolar plate according to claim 3, characterized in that: The metal bipolar plate is placed in an ion plating machine, and the metal bipolar plate, the vacuum chamber of the ion plating machine and the rotating rack are baked and degassed. After the metal bipolar plate is placed in the ion plating machine, a mechanical pump and a molecular pump group are turned on to evacuate the vacuum, and heating is turned on. The heating temperature is 150° C. to 200° C., and the baking time is 1 h to 2 h; and / or, When the metal bipolar plate is subjected to plasma etching and cleaning, the power of the ion source is 2 kW to 3 kW, the flow rate of argon gas is 300 sccm to 500 sccm, the bias voltage is 500 V to 600 V, and the time is 0.5 h to 1 h.

10. A fuel cell, characterized in that: A bipolar plate manufactured by the method for manufacturing a fuel cell bipolar plate according to any one of claims 1 to 9.